Mindfulness-Based Interventions in the Treatment of Psychosis: A Narrative Systematic Review - DiGiacomo, Anthony; Moll, Sandra; MacDermid, Joy; Law, Mary (Canadian Journal of Counselling and Psychotherapy, 2016)
Although there is a growing body of research on the value of mindfulness for a range of mental health conditions, evidence regarding mindfulness for individuals with psychosis is much more limited. The purpose of this article was to conduct a narrative systematic review of randomized controlled trials evaluating the effectiveness of mindfulness-based techniques with individuals experiencing symptoms of psychosis. Eligibility criteria for the studies included random allocation, a focus on participants with psychosis, implementation of mindfulness-based interventions, and inclusion of a control group. A majority of measures across studies showed no significant treatment effect. Therefore, studies to date do not indicate that mindfulness-based interventions have an impact on symptoms of psychosis. Across trials, mindfulness interventions varied greatly. Furthermore, mindfulness interventions were designed to help individuals cope with symptoms and not necessarily to make them go away. Therefore, future studies should consider measuring functional outcomes, not symptom-related outcomes.